Makna pada Tradisi Manyabik Padi Sarentak di Nagari Sumpur Kudus, Sumatera Barat - Arianti, Virma Dwi; Kahanna, Mutia; Oktayanty, Yetty (Asosiasi dosen IDEBAHASA KEPRI, 2023)
The aimed of this research is to describe the implementation and meaning of the Manyabik Padi Sarentak tradition in Nagari Sumpur Kudus, Sijunjung Regency, West Sumatra Province. The theory used in this research is the symbolic interpretive theory of Clifford Geerzt. The method used is a qualitative method, with data collection techniques of observation, interviews and documentation. The results of the research show that the background of the Manyabik Padi Sarentak tradition, apart from reducing pests, is also related to the arrival of Sheikh Ibrahim to Sumpur Kudus in 1503, where he taught the community to open rice fields, plow and plant rice, but inwardly taught the Islamic religion. The order of implementation of the Manyabik Padi Sarentak tradition is the meeting to determine palakat, Manyabik Padi, Maangkuik Padi Ka Ungguak, Mangiriak Ungguak Padi, Mangipeh Padi, Manjomuagh Padi, Bakawuagh Adat, and Mamanggang Jami. The general meaning of this tradition is togetherness in the context of the time it started. The meaning of implementing this tradition is a process of equalizing perceptions, economic meaning and employment opportunities, community adaptation to technology, local wisdom, expressions of gratitude and simplicity, tolerance and tolerance.